Chemical, Mineralogical, and Morphological Properties of Steel Slag - Irem Zeynep Yildirim; Monica Prezzi (Advances in Civil Engineering)
Steel slag is a byproduct of the steelmaking and steel refining processes. This paper provides an overview of the different types of steel slag that are generated from basic-oxygen-furnace (BOF) steelmaking, electric-arc-furnace (EAF) steelmaking, and ladle-furnace steel refining processes. The mineralogical and morphological properties of BOF and electric-arc-furnace-ladle [EAF(L)] slag samples generated from two steel plants in Indiana were determined through X-Ray Diffraction (XRD) analyses and Scanning Electron Microscopy (SEM) studies. The XRD patterns of both BOF and EAF(L) slag samples were very complex, with several overlapping peaks resulting from the many minerals present in these samples. The XRD analyses indicated the presence of free MgO and CaO in both the BOF and EAF(L) slag samples. SEM micrographs showed that the majority of the sand-size steel slag particles had subangular to angular shapes. Very rough surface textures with distinct crystal structures were observed on the sand-size particles of BOF and EAF(L) slag samples under SEM. The characteristics of the steel slag samples considered in this study are discussed in the context of a detailed review of steel slag properties.